The role of neurotrophic factors in retinal ganglion cell resiliency - Abraham, Alan K.; Telias, Michael (Frontiers in Cellular Neuroscience, 2025)
Many retinal diseases are characterized by direct or indirect retinal ganglion cell (RGC) neurodegeneration. In glaucoma and optic nerve neuropathies, RGCs are the primary affected cells, whereas in photoreceptor dystrophies, RGC loss is secondary to the death of rods and cones. The death of RGCs in either case will irreversibly cause loss of vision, as RGCs are the sole output neurons of the retina. RGC neurodegeneration affects certain neurons preferentially, resulting in subpopulations of resilient and susceptible cells. Neurotrophins (NTs) are known to mediate neuronal survival through the downstream activation of various anti-apoptotic pathways. In this review, we summarize the current methods of RGC identification and quantification in animal models of direct or indirect neurodegeneration, and describe the advantages and disadvantages associated with these techniques. Using these techniques, multiple studies have uncovered the potential role of NTs in protecting RGCs during direct neurodegeneration, with BDNF and NGF delivery promoting RGC survival in models of experimental glaucoma. Many fewer studies have addressed similar questions in retinal diseases where RGC loss is secondary to photoreceptor degeneration, yielding conflicting results. Our analysis suggests that these seemingly contradictory results can be explained by the varying onset and geographic distribution of photoreceptor death.